2015
DOI: 10.1186/s13099-015-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of caffeine with the SOS response pathway in Escherichia coli

Abstract: BackgroundPrevious studies have highlighted the antimicrobial activity of caffeine, both individually and in combination with other compounds. A proposed mechanism for caffeine’s antimicrobial effects is inhibition of bacterial DNA repair pathways. The current study examines the influence of sub-lethal caffeine levels on the growth and morphology of SOS response pathway mutants of Escherichia coli.MethodsGrowth inhibition after treatment with caffeine and methyl methane sulfonate (MMS), a mutagenic agent, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Also well-known is the accumulation of inviable cells in cultures treated with bilayer compacters such as nicotine 79 , or caffeine 80 . Although this bactericidal action is classically explained as a lethal genetic effect of fatty compounds 76 , 81 , our experiments reveal causality between lipid compaction and decreased growth rates under effective membrane stiffening.…”
Section: Discussionmentioning
confidence: 66%
“…Also well-known is the accumulation of inviable cells in cultures treated with bilayer compacters such as nicotine 79 , or caffeine 80 . Although this bactericidal action is classically explained as a lethal genetic effect of fatty compounds 76 , 81 , our experiments reveal causality between lipid compaction and decreased growth rates under effective membrane stiffening.…”
Section: Discussionmentioning
confidence: 66%
“…Gene uvrA, uvrB dan uvrC work to excision nucleotide repair, especially uvrC which changes damage nucleotide with correct nucleotide. The study showed caffeine only inhibits uvrC gene with decrease synthesis trans-lesion in DNA cell 16 .…”
Section: Resultsmentioning
confidence: 90%
“…The research found caffeine inhibit DNA replication which need gen repaired by gen recA, recB, recC 15 AlkA, YzaB, Ogt, KsgA. In other study, Whitney and Weir showed caffeine potentiates methyl methane sulfonate (MMS) inhibit Escherichia coli with disrupt SOS Pathway in Escherichia coli 16 . SOS Pathway is mechanism DNA repair to prevents further damage 17 .…”
Section: Resultsmentioning
confidence: 94%
“…A search on PubMed revealed that two of the highly indexed phytochemicals (caffeine and ricinine) have already been tested experimentally and confirmed as antibacterial agents ( 35 ). Caffeine has been reported to exert physiological effects on various organisms at µM concentrations and to act as an antimicrobial agent ( 36 , 37 ). Ricinine had high nematocidal activity ( 38 ) and notable activity against ants ( 39 ).…”
Section: Resultsmentioning
confidence: 99%